Biochemical and Morphological Assessment of Rabi Sorghum Genotypes for Shootfly Resistance - Baravkar, S.A.; Dalvi, U. S.; Totre, A. S.; Shinde, M. S.; Naik, R. M.; Kale, A. A. (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was conducted at Sorghum Improvement Project and Department of Biochemistry, Mahatma Phule Krishi Vidyapeeth, Rahuri, Maharashtra, India during rabi 2019–20 for assessment of rabi sorghum genotypes for shootfly through biochemical perspective. Sorghum is an important food and fodder crop of dry land agriculture. The experimental material consisted of 11 sorghum genotypes viz; RSV 1628, RSV 1023, RSV 1910, RSV 2371, RSV 1945, RSV 1838, RSV 2025, RSV 1918, RSV 1988, RSV 2391, RSV 1941, three varieties viz., Phule Vasudha, Phule Revati, M-35-1, three shootfly resistant checks viz., RSV 1188, IS 18551, RSE 3 and a susceptible check i.e. DJ 6514. The experiments were conducted under pot culture and field conditions at different stages. Resistance against shootfly in sorghum was governed by the physical and chemical genes. The morphological characters like trichome density, oviposition and dead heart percentage and biochemical attributes like polyphenol oxidase, peroxidise and chlorophyll content can be used as marker traits in shootfly resistance breeding programme to broaden the genetic base and increase the levels of resistance to sorghum. The sorghum genotype RSE 3, RSV 1945, RSV 1941, RSV 1188, and RSV 2371 recorded higher polyphenol oxidase activity at 28 DAE as compared to other genotypes. So, these sorghum genotypes are good source for shootfly resistance breeding. The genotype RSE 03, RSV 1941 and RSV 1188 exhibited positive results for shootfly resistance and can be used as donor for shootfly breeding programme.